A novel preparation of solid amine sorbents for enhancing CO2 adsorption capacity using alumina-extracted waste. (1st June 2022) - Li, Xiangyu; Wang, Zhiqing; Liu, Zheyu; Feng, Ru; Song, Shuangshuang; Huang, Jiejie; Fang, Yitian
Abstract: A "wet gel impregnation" method (WGI) was applied to prepare modified CO2 sorbents derived from alumina-extracted residue of coal ash (AR). Tetraethylene pentamine (TEPA) was selected as an amine polymer and it was evenly dispersed on the surface of AR. And the effects of loading amount, impregnation method, and adsorption temperature on CO2 adsorption capacity of the sorbent were investigated by thermogravimetric analyzer (TGA). The results showed that the desired sorbent with 60% TEPA loading via WGI had the maximum CO2 adsorption capacity of 3.45 mmol/g under 100% CO2 at 75 °C. This was attributed to the fact that the loading in wet gel state dramatically improved TEPA dispersion on the supports and increased the saturated loading of amine. Moreover, the sorbent still maintained stable CO2 uptake after five repeated adsorption-desorption cycles. These results suggested that amine-impregnated AR sorbent synthesized by WGI was an excellent and low-cost sorbent for CO2 capture. Graphical abstract: Image 1 Highlights: ● Alumina-extracted residue of coal ash was used to prepare CO2 sorbents for the first time. ● Low-cost sorbents with excellent capture capacity was prepared by novel wet gel impregnation. ● The mechanism of wet gel impregnation promoting CO2 adsorption performance was elaborated.